2023
DOI: 10.1002/cam4.6307
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve of trans‐areola single‐site endoscopic thyroidectomy in a high‐volume center: A CUSUM‐based assessment

Abstract: BackgroundLimited attempts have been made in trans‐areola single‐site endoscopic thyroidectomy (TASSET) due to technical challenges and the lengthy time for proficiency. This study aimed to define the learning curve of TASSET and to describe improvements in operative performance over time.MethodsBased on 222 consecutive TASSET procedures, the learning curve was established according to the operation time by using cumulative sum analysis (CUSUM). The end‐point of learning curve was defined as the number of case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…CUSUM analysis was employed to better define the learning curve of TASSEP, and the turning point was identified as case 17 (Figure 5B ). 47 After the end‐point of the learning curve, the operation time of TASSEP significantly improved from 90.41 ± 12.34 min (case 1–17) to 73.74 ± 4.34 min (case 17–40). EBL was evaluated using dry medical gauze strips (0.5 × 5 cm), and did not differ significantly between TASSEP and COP (20.42 ± 10.21 mL vs. 18.86 ± 12.59 mL, p = 0.649).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…CUSUM analysis was employed to better define the learning curve of TASSEP, and the turning point was identified as case 17 (Figure 5B ). 47 After the end‐point of the learning curve, the operation time of TASSEP significantly improved from 90.41 ± 12.34 min (case 1–17) to 73.74 ± 4.34 min (case 17–40). EBL was evaluated using dry medical gauze strips (0.5 × 5 cm), and did not differ significantly between TASSEP and COP (20.42 ± 10.21 mL vs. 18.86 ± 12.59 mL, p = 0.649).…”
Section: Resultsmentioning
confidence: 92%
“…In current study, 17 cases were required to qualify for the initial surgical proficiency stage in TASSEP. Whereas the end point of the learning curve in trans‐areola single site endoscopic thyroidectomy (TASSET) was case 41, which indicated that the surgeons could adopt TASSEP more quickly than TASSET, making it a promising alternative to open surgery for both surgeons and patients 47 . Therefore, in line with the standardized TASSEP procedure, technique challenges could be overcome readily with reliable operational precision and safety.…”
Section: Discussionmentioning
confidence: 99%